MOLECULAR DOCKING STUDY OF EPIGALLOCATECHIN GALLATE (EGCG) AS A THERAPY FOR TYPE 2 DIABETES MELLITUS - Wijianto, Bambang; Arief, Ihsahnul; Yohana, Vanesha (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
Epigallocatechin gallate (EGCG) has an effect in reducing sugar levels in the blood by inhibiting α-glucosidase enzyme, which is connected explicitly by hydrogen bonds and modifies the secondary structure and micro-environment of the enzyme reversibly and non-competitive. This study looks at the activity and interaction of EGCG as α-glucosidase inhibitors in the form of binding affinity and compound bonding profiles with receptors, including toxicity predictions and drug-likeness results. The research was performed in silico with molecular docking on Autodock Vina that integrated through PyRx, then viewed the compound's binding profile with receptor using Discovery Studio 2021 Client, toxicity prediction using ProTox-II and determination of drug-likeness using SwissADME based on Lipinski's rule of five guidelines. The control drugs used were acarbose and miglitol. The molecular docking results obtained that the binding affinity of EGCG is -8.4 kcal/mol while acarbose and miglitol are -13.8 kcal/mol and -5.3 kcal/mol respectively. There are amino acid residues similar to the drug control with various interactions like electrostatic, hydrophobic, and hydrogen bonds; then it has an inactive target for each toxicity parameter and has a molecular weight of 458.37 g/mol; Log P value of 1.01; H-bond donor of 8; and H-bond acceptor of 11 in the determination of drug-likeness. Based on these results, EGCG has effectiveness as α-glucosidase inhibitors predicted to be non-toxic; however, there are violations in determining drug-likeness.